Translation, Cross-Cultural Adaptation to Malay, and psychometric evaluation of the AIM-IAM-FIM questionnaire: Measuring the implementation outcome of a community-based intervention programme - Hazeqa Salleh; Richard Avoi; Haryati Abdul Karim; Suhaila Osman; Nirmal Kaur Singh; Prabakaran Dhanaraj (San Francisco, CA : Public Library of Science, 2023)
Background The implementation outcomes determine the success and progress of a community-based intervention programme. The community is an important stakeholder whose effects should be assessed. Nevertheless, Malaysia has limited instruments for determining outcome measurements. This research aimed to develop Malay versions of the Acceptability, Appropriateness, and Feasibility Intervention Measures (AIM-IAM-FIM) questionnaire, which evaluates the implementation outcome of the programme. Methods A methodological study of the translation and validation of the implementation outcome measures was conducted from March 2022 until December 2022. Three key analyses were conducted: (1) translation and validation; (2) factor investigation and extraction (n = 170); and (3) scale evaluation (n = 235). Result The Malay version measuring the implementation outcome measures of a communitybased intervention programme was produced after extensive translation and modification, and it consisted of a single dimension with seven items. The content validity index was 0.9, the exploratory factor analysis showed that the KMO measure of sample adequacy was 0.9277, and Bartlett’s sphericity test was statistically significant. Cronbach’s alpha was good, with a level of 0.938. The single factor structure fitted the data satisfactorily [χ2 (pvalue of 0.002), SRMR = 0.030, CFI = 0.999, RMSEA = 0.079, TLI = 0.998]. Factor loading for all items was > 0.7. Conclusion The 7-item Malay version of the AIM-IAM-FIM survey instrument is valid and reliable for assessing the acceptability of a community-based intervention study and is applicable to other fields. Future studies in psychometric evaluation are recommended in other states due to the variety of Malay dialects spoken across Asia. The scale may also benefit other areas where the language is spoken.